Principles and practices of assessment : a guide for assessors in the FE and skills sector - Gravells, Ann (SAGE ; Learning Matters, 2016)
This new third edition, updated in line with recent changes and qualification in the further education and skills sector provides you with all the information you need to complete the assessment units for the Award and Certificate in Education and Training or the assessment part of the TAQA qualification.